2018
DOI: 10.1186/s13058-018-0946-6
|View full text |Cite
|
Sign up to set email alerts
|

The amino acid transporter SLC7A5 confers a poor prognosis in the highly proliferative breast cancer subtypes and is a key therapeutic target in luminal B tumours

Abstract: BackgroundBreast cancer (BC) is a heterogeneous disease characterised by variant biology and patient outcome. The amino acid transporter, SLC7A5, plays a role in BC although its impact on patient outcome in different BC subtypes remains to be validated. This study aimed to determine whether the clinicopathological and prognostic value of SLC7A5 is different within the molecular classes of BC.MethodsSLC7A5 was assessed at the genomic level, using Molecular Taxonomy of Breast Cancer International Consortium (MET… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
96
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 56 publications
9
96
0
Order By: Relevance
“…Finally, we show that LAT1 overexpression is consistently associated with poor relapse free survival in four independent clinical datasets from ER+ patients that received an endocrine therapy. This observation is consistent with other reports that LAT1 may be an indicator of poor prognosis 25,61 . Taken together with the mechanistic outcomes reported here, further study of LAT1 and its role in endocrine therapy resistance may lead to novel therapeutic alternatives to improve overall survival for patients.…”
Section: Discussionsupporting
confidence: 94%
“…Finally, we show that LAT1 overexpression is consistently associated with poor relapse free survival in four independent clinical datasets from ER+ patients that received an endocrine therapy. This observation is consistent with other reports that LAT1 may be an indicator of poor prognosis 25,61 . Taken together with the mechanistic outcomes reported here, further study of LAT1 and its role in endocrine therapy resistance may lead to novel therapeutic alternatives to improve overall survival for patients.…”
Section: Discussionsupporting
confidence: 94%
“…16,17 The data on HER2 were already available for this early-stage BC cohort, and details of staining and scoring were included in previous publications. [18][19][20][21] Survival data were previously retrieved and updated, including: (i) BC-specific survival (BCSS), defined as the time (in months) from the date of primary surgical treatment to the time of death from BC; and (ii) distant metastasis-free survival (DMFS), defined as the time from the surgery until the first distant metastasis. In this study, post-recurrence survival was defined as the time (in months) from the date of surgical removal of the recurrent tumour to the date of death from BC.…”
Section: S T U D Y C O H O R Tmentioning
confidence: 99%
“…This is particularly interesting as the luminal B subtype (ER+ subtype) has aggressive clinical behavior, with prognosis similar to that of HER2-enriched and basal-like group and a lower sensitivity to endocrine treatment compared to luminal A ER+ breast cancer (59). Interestingly, recent studies showed that a high expression of different AA transporters, such as SLC3A2 or SLC7A5, is related to poor outcomes in luminal B ER+ breast cancer subtype (60, 61). These data suggest that this subtype might be particular vulnerable to glutamine depletion.…”
Section: Discussionmentioning
confidence: 99%